Laminated ion thermoelectric gel battery and preparation method and application thereof
By building a stacked ionic thermoelectric gel battery, adjusting the concentration of redox pairs and water-soluble metal salts, the problem of low output power density of the existing ionic thermoelectric gel system is solved, and efficient thermoelectric conversion performance is achieved, suitable for small sensors and wearable devices.
Patent Information
- Application Number
- CN202510017569.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-05-02
AI Technical Summary
Although the existing ionic thermoelectric gel system has an ultra-high thermal potential, its output power density is relatively low and it cannot independently support the work of small sensors or other small electronic devices, which seriously restricts its market-oriented application.
The ionic thermoelectric gel battery adopts a stacked structure. By setting the electrode, the ionic thermoelectric gel 1, the built-in electrode, the ionic thermoelectric gel 2 and the electrode 2 in turn, the concentration of different types of redox pairs and water-soluble metal salts is adjusted to build a stacked structure to improve the thermoelectric conversion performance.
The output power density and thermoelectric potential value of the stacked ionic thermoelectric gel battery is significantly improved, with the output power density reaching 600mW m-2 and the thermoelectric potential of 8.5mV K-1, which is suitable for small sensors and wearable electronic devices.
Smart Images

Figure CN119923182A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermoelectric materials, and in particular relates to a laminated ion thermoelectric gel battery and a preparation method and application thereof. Background Art
[0002] In response to the needs of green and low-carbon development, thermoelectric conversion technology is a green and environmentally friendly energy conversion technology with the advantages of being environmentally friendly, having no moving parts, low noise, and easy to miniaturize. Thermoelectric conversion technology can directly convert thermal energy in the surrounding environment into electrical energy, and is expected to free hundreds of billions of sensors and electronic devices from the constraints of the power grid or batteries to achieve self-power supply, reducing costs and energy consumption.
[0003] Compared with traditional semiconductor electronic thermoelectric materials, ionic thermoelectric gel uses ions as energy carriers and has an ionic thermoelectric potential of up to mV / K, which is hundreds of times higher than that of electronic thermoelectric materials. It can collect low-grade waste heat (<100℃) in the environment and convert it directly into electrical energy. Ionic thermoelectric gel also has good mechanical properties such as flexibility and stretchability, and is environmentally friendly, low-cost, and simple to prepare. It has broad application prospects in the field of wearable electronic devices such as the Internet of Things. Ionic thermoelectric gel batteries have two thermoelectric conversion mechanisms, namely thermoelectrochemical effect and thermal diffusion effect. Thermoelectrochemical effect refers to the oxidation or reduction reaction of redox pairs of ions at the hot and cold electrodes under temperature difference, and the direct conversion of heat to electricity is achieved through the entropy change before and after the reaction. The thermal diffusion effect refers to the directional migration of anions and cations under temperature difference to produce a diffusion concentration difference and then induce a potential difference, realizing the direct conversion of heat to electricity. At present, although the ionic thermoelectric gel system has an ultra-high thermoelectric potential, its output power density is low and it still cannot independently support the operation of small sensors or other small electronic devices, which seriously restricts its further market application. Therefore, improving the output power density of ionic thermoelectric gel has become the key to the market application of ionic thermoelectric gel system. Summary of the invention
[0004] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a laminated ion thermoelectric gel battery. The second purpose of the present invention is to provide a method for preparing the above-mentioned laminated ion thermoelectric gel battery. The third purpose of the present invention is to provide a temperature difference power generation device. In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:
[0005] The first aspect of the present invention provides a laminated ion thermoelectric gel battery, comprising an electrode 1, an ion thermoelectric gel 1, a built-in electrode, an ion thermoelectric gel 2 and an electrode 2 arranged in sequence; the raw materials for preparing the ion thermoelectric gel 1 include a gelling matrix, a water-soluble metal salt 1, a redox couple 1 and water; the raw materials for preparing the ion thermoelectric gel 2 include a gelling matrix, a redox couple 2 and water; the redox couple 1 is of a different type from the redox couple 2.
[0006] Preferably, the redox pair 1 and the redox pair 2 are independently selected from K 3 Fe(CN) 6 / K 4 Fe(CN) 6 Or Na 2 SO 4 / Na 2 SO 3 .
[0007] More preferably, the redox couple 1 is Na 2 SO 4 / Na 2 SO 3 .
[0008] More preferably, the redox couple 2 is K 3 Fe(CN) 6 / K 4 Fe(CN) 6
[0009] Preferably, the gelling matrix is selected from at least one of gelatin, polyvinyl alcohol, carrageenan, chitosan and polyacrylamide.
[0010] The laminated ion thermoelectric gel battery material of the present invention uses an organic matrix with good flexibility as a gel matrix, so that the prepared ion thermoelectric gel material is a flexible gel with excellent tensile properties, and is suitable for preparing flexible ion gel thermoelectric conversion devices and flexible temperature difference power generation devices.
[0011] Preferably, the water-soluble metal salt 1 is selected from inorganic metal salts or organic metal salts.
[0012] Preferably, the raw materials for preparing the ionic thermoelectric gel 2 also include a water-soluble metal salt 2; the concentration of the water-soluble metal salt 1 in the ionic thermoelectric gel 1 is greater than the concentration of the water-soluble metal salt 2 in the ionic thermoelectric gel 2; the water-soluble metal salt 2 is selected from an inorganic metal salt or an organic metal salt.
[0013] More preferably, the inorganic metal salt is at least one of sodium chloride, potassium chloride, potassium nitrate and potassium sulfate; the organic metal salt is at least one of potassium trifluoromethanesulfonate, potassium citrate and sodium oxalate.
[0014] Preferably, the usage ratio of the gel matrix to the redox couple 1 is 1 g: (1-10) mmol.
[0015] Preferably, the usage ratio of the gel matrix to the water-soluble metal salt 1 is 1 g: (1-10) mmol.
[0016] Preferably, the usage ratio of the gel matrix to water is 1 g: (5-20) mL.
[0017] Preferably, the usage ratio of the gel matrix to the redox couple 2 is 1 g: (0.3-2) mmol.
[0018] Preferably, the usage ratio of the gel matrix to water is 1 g: (2-5) mL.
[0019] Preferably, the K 3 Fe(CN) 6 / K 4 Fe(CN) 6 Middle K 3 Fe(CN) 6 With K 4 Fe(CN) 6 The molar ratio is 1:(0.5-10).
[0020] More preferably, the K 3 Fe(CN) 6 The dosage ratio of K to water is (0.01-0.50) mol: 1L. 4 Fe(CN) 6 The dosage ratio with water is (0.02-0.70) mol:1L.
[0021] Preferably, the Na 2 SO 4 / Na 2 SO 3 ZhongNa 2 SO 4 with Na 2 SO 3 The molar ratio is 1:(0.5-5).
[0022] More preferably, the Na 2 SO 4 The dosage ratio of Na to water is (0.10-0.70) mol: 1L. 2 SO 3 The dosage ratio with water is (0.10-0.70) mol:1L.
[0023] Preferably, the electrode 1 and the electrode 2 are independently selected from at least one of graphite paper, carbon paper and carbon cloth.
[0024] Preferably, the built-in electrode is selected from at least one of graphite paper, carbon paper, carbon cloth, and a cation exchange membrane.
[0025] Preferably, the operating temperature range of the ionic thermoelectric gel 1 or the ionic thermoelectric gel 2 is 10-80°C.
[0026] More preferably, the operating temperature range is 15-60°C.
[0027] More preferably, the operating temperature range is 20-40°C.
[0028] The second aspect of the present invention provides a method for preparing the laminated ion thermoelectric gel battery of the first aspect, comprising the following steps:
[0029] After placing the ionic thermoelectric gel 1 on the surface of the electrode 1, the built-in electrode is covered on the surface of the ionic thermoelectric gel 1 away from the electrode 1, the ionic thermoelectric gel 2 is arranged on the surface of the built-in electrode away from the ionic thermoelectric gel 1, and the electrode 2 is arranged on the surface of the ionic thermoelectric gel 2 away from the built-in electrode, to obtain a laminated ionic thermoelectric gel battery with the electrode, ionic thermoelectric gel 1, built-in electrode, ionic thermoelectric gel 2 and electrode 2 arranged in sequence.
[0030] Preferably, the method for preparing the ionic thermoelectric gel 1 comprises the following steps: mixing a gelling matrix, a water-soluble metal salt 1 and a redox couple 1 in water to obtain a paste gel 1, and then preparing the ionic thermoelectric gel 1.
[0031] More preferably, the mixing to form the pasty gel 1 is performed at 60-100°C.
[0032] More preferably, the gel matrix of the paste gel 1 is polyvinyl alcohol, and the paste gel 1 is subjected to a freeze-thaw cycle to obtain the ionic thermoelectric gel 1 .
[0033] More preferably, the freezing is refrigeration at -20°C.
[0034] More preferably, the freezing time is 20-30 hours.
[0035] Preferably, the preparation method of the ionic thermoelectric gel 2 comprises the following steps: mixing the gel matrix and the redox couple 2 in water to obtain a paste gel 2, and then preparing the ionic thermoelectric gel 2
[0036] More preferably, the mixing to form the pasty gel 2 is performed at 60-100°C.
[0037] Preferably, the method specifically includes: injecting the ionic thermoelectric gel 1 into a mold and covering it with a built-in electrode, setting a mold on the other side of the built-in electrode, injecting the ionic thermoelectric gel 2 into the mold and placing it on the other side of the built-in electrode, and finally covering it with the electrode 2 to form a laminated structure of electrode 1-ionic thermoelectric gel 1-built-in electrode-ionic thermoelectric gel 2-electrode 2.
[0038] More preferably, the material of the mold is polydimethylsiloxane.
[0039] The third aspect of the present invention provides a temperature difference power generation device, comprising the laminated ion thermoelectric gel battery of the first aspect.
[0040] Preferably, the number of the laminated ion thermoelectric gel batteries in the temperature difference power generation device is one or more.
[0041] More preferably, when there are a plurality of stacked ion thermoelectric gel batteries, the ion thermoelectric gel batteries are sequentially connected in series.
[0042] Further preferably, the laminated ion thermoelectric gel batteries are connected in series via copper conductive glue.
[0043] The beneficial effects of the present invention are:
[0044] (1) The present invention provides a laminated ion thermoelectric gel battery, comprising an electrode, an ion thermoelectric gel 1, a built-in electrode, an ion thermoelectric gel 2 and an electrode arranged in sequence. The ion thermoelectric gel battery with a laminated structure has good thermoelectric conversion performance compared to a single-layer ion thermoelectric gel battery, and can obtain excellent output power density and thermoelectric potential by adjusting the concentration of redox couples and water-soluble metal salts in two different types of gels. The output power density and thermoelectric potential of the laminated ion thermoelectric gel battery material of the present invention are significantly improved compared to traditional thermoelectric gel batteries, and the corresponding thermoelectric potential is 8.5mV K -1 In addition, the output power density can reach 600mW m at a temperature difference of 5K. -2 The laminated ion thermoelectric gel battery material of the present invention uses an organic matrix with good flexibility as a gel matrix, so that the prepared ion thermoelectric gel material is a flexible gel with excellent tensile properties, and is suitable for preparing flexible ion gel thermoelectric conversion devices and flexible temperature difference power generation devices.
[0045] (2) The present invention provides a temperature difference power generation device composed of the above-mentioned laminated ion thermoelectric gel battery. When placed at a temperature of 313K and a temperature difference of 5K is applied to the hot end and the cold end, the output voltage obtained is 1.355V and the output power density obtained is 130mW m -2The temperature difference power generation device has the advantages of small size, large output voltage, high power, and high energy conversion efficiency, and can be further made into wearable equipment with good flexibility and ductility. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 It is a schematic diagram of the laminated ion thermoelectric gel battery of the present invention;
[0047] Figure 2 This is a real picture of the plasticization of the laminated ion thermoelectric gel battery material in Example 1 of the present invention;
[0048] Figure 3 A bar graph showing the ion thermoelectric potential value of the laminated ion thermoelectric gel battery of the present invention;
[0049] Figure 4 This is a graph showing the output power density of the laminated ion thermoelectric gel battery of the present invention at a temperature difference of 5K;
[0050] Figure 5 This is a diagram of energy density recovered by the laminated ion thermoelectric gel battery of the present invention at a temperature difference of 5K;
[0051] Figure 6 Schematic diagram of device voltage of a temperature difference power generation device made by connecting 9 stacked ion thermoelectric gel batteries in Example 1 in series under a temperature difference of 5K, wherein the inset is a temperature difference power generation device made by connecting 9 stacked ion thermoelectric gel batteries in series;
[0052] Figure 7 The output power density curve of the temperature difference power generation device made by connecting 9 stacked ion thermoelectric gel batteries of Example 1 in series. DETAILED DESCRIPTION
[0053] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.
[0054] Example 1
[0055] This embodiment provides a laminated ion thermoelectric gel battery, and the preparation method thereof is as follows:
[0056] (1) 3 g of gelatin, 0.0659 g of potassium ferrocyanide (final concentration of 0.025 mol / L), and 0.5912 g of potassium ferrocyanide (final concentration of 0.175 mol / L) were weighed and added to 8 mL of Wahaha water to obtain a mixture; then, the mixture was heated at 70° C. and stirred at 980 rpm until it dissolved and formed a viscous liquid;
[0057] (2) Weigh 0.5 g polyvinyl alcohol, 0.1775 g sodium sulfate (final concentration of 0.25 mol / L), 0.1575 g sodium sulfite (final concentration of 0.25 mol / L), and 0.3763 g potassium trifluoromethanesulfonate (final concentration of 0.40 mol / L), add 5 mL of Wahaha water, stir at 90 ° C for 2 h, mix well, transfer to a 5×5×0.2 cm polydimethylsiloxane mold, and then place it at -20 ° C for 24 h, thaw at room temperature for 3 h to obtain polyvinyl alcohol (PVA) hydrogel, and then cut it into 1×1×0.2 cm hydrogel cubes;
[0058] (3) placing a polydimethylsiloxane mold with a size of 1×1×0.2 cm on a gold-sprayed graphite electrode, injecting the uniform viscous solution of step (1) into the mold, and covering it with a cation exchange membrane, placing another silicone mold on the above cation exchange membrane, placing the hydrogel cube cut from step (2) into the mold, and finally covering it with a gold-sprayed graphite electrode to form an electrode sheet-ion thermoelectric gel-cation exchange membrane-ion thermoelectric gel-electrode sheet stacking structure (such as Figure 1 As shown), and finally encapsulated with polyethylene film to obtain a laminated ion thermoelectric gel battery.
[0059] The flexibility of the laminated ionic thermoelectric gel in Example 1 of the present invention is shown as follows Figure 2 As shown, Figure 2 (a) is the stretched state of the laminated ionic thermoelectric gel. Figure 2 (b) is the bending state of the stacked ionic thermoelectric gel. Figure 2 (c) is the twisted state of the stacked ionic thermoelectric gel. Figure 2 (d) is the twisted and stretched state of the layered ionic thermoelectric gel; the layered ionic thermoelectric gel of the present invention does not break under the stretching, bending, twisting, and twisted and stretched states, which shows that the gel of the present invention has good flexibility.
[0060] Example 2
[0061] This embodiment provides a laminated ion thermoelectric gel battery, and the preparation method thereof is as follows:
[0062] (1) 3 g of gelatin, 0.0659 g of potassium ferrocyanide (final concentration of 0.025 mol / L), and 0.5912 g of potassium ferrocyanide (final concentration of 0.175 mol / L) were weighed and added to 8 mL of Wahaha water to obtain a mixture; then, the mixture was heated at 70° C. and stirred at 980 rpm until it dissolved and formed a viscous liquid;
[0063] (2) Weigh 0.5 g of polyvinyl alcohol, 0.1775 g of sodium sulfate (final concentration of 0.25 mol / L), 0.1575 g of sodium sulfite (final concentration of 0.25 mol / L), and 0.202 g of potassium nitrate (final concentration of 0.40 mol / L), add 5 mL of Wahaha water, stir at 90 ° C for 2 h, mix well and transfer to a 5×5×0.2 cm mold, then place it at -20 ° C for 24 h, thaw at room temperature for 3 h to obtain polyvinyl alcohol (PVA) hydrogel, and then cut it into 1×1×0.2 cm hydrogel cubes;
[0064] (3) placing a silicone mold with a size of 1×1×0.2 cm on a gold-sprayed graphite electrode, injecting the uniform viscous solution of step (1) into the mold, and covering it with a cation exchange membrane, placing another silicone mold on the above cation exchange membrane, placing the hydrogel cube cut from step (2) into the mold, and finally covering it with a gold-sprayed graphite electrode to form an electrode sheet-ion thermoelectric gel-cation exchange membrane-ion thermoelectric gel-electrode sheet stacking structure (such as Figure 1 As shown), and finally encapsulated with polyethylene film to obtain a laminated ion thermoelectric gel battery.
[0065] Example 3
[0066] This embodiment provides a laminated ion thermoelectric gel battery, and the preparation method thereof is as follows:
[0067] (1) 3 g of gelatin, 0.0659 g of potassium ferrocyanide (final concentration of 0.025 mol / L), and 0.5912 g of potassium ferrocyanide (final concentration of 0.175 mol / L) were weighed and added to 8 mL of Wahaha water to obtain a mixture; then, the mixture was heated at 70° C. and stirred at 980 rpm until it dissolved and formed a viscous liquid;
[0068] (2) Weigh 0.5 g of polyvinyl alcohol, 0.1775 g of sodium sulfate (final concentration of 0.25 mol / L), 0.1575 g of sodium sulfite (final concentration of 0.25 mol / L), and 0.1491 g of potassium chloride (final concentration of 0.40 mol / L), add 5 mL of Wahaha water, stir at 90 ° C for 2 h, mix well and transfer to a 5×5×0.2 cm mold, then place it at -20 ° C for 24 h, thaw at room temperature for 3 h to obtain polyvinyl alcohol (PVA) hydrogel, and then cut it into 1×1×0.2 cm hydrogel cubes;
[0069] (3) placing a silicone mold with a size of 1×1×0.2 cm on a gold-sprayed graphite electrode, injecting the uniform viscous solution of step (1) into the mold, and covering it with a cation exchange membrane, placing another silicone mold on the above cation exchange membrane, placing the hydrogel cube cut from step (2) into the mold, and finally covering it with a gold-sprayed graphite electrode to form an electrode sheet-ion thermoelectric gel-cation exchange membrane-ion thermoelectric gel-electrode sheet stacking structure (such as Figure 1 As shown), and finally encapsulated with polyethylene film to obtain a laminated ion thermoelectric gel battery.
[0070] Comparative Example 1
[0071] This comparative example provides a laminated ion thermoelectric gel battery, and its preparation method is as follows:
[0072] (1) 3 g of gelatin, 0.0659 g of potassium ferrocyanide (final concentration of 0.025 mol / L) and 0.5912 g of potassium ferrocyanide (final concentration of 0.175 mol / L) were weighed, and 8 mL of Wahaha water was added to obtain a mixture; then, the mixture was placed at 70° C. and heated with stirring at 310 rpm until it dissolved and formed a viscous liquid;
[0073] (2) Weigh 0.5 g of polyvinyl alcohol, 0.0852 g of sodium sulfate (final concentration of 0.12 mol / L), and 0.0756 g of sodium sulfite (final concentration of 0.12 mol / L), add 5 mL of Wahaha water, stir at 90 °C for 2 h, mix well, transfer to a 5 × 5 × 0.2 cm mold, and then place it at -20 °C for 24 h, thaw at room temperature for 3 h to obtain polyvinyl alcohol (PVA) hydrogel, and then cut it into 1 × 1 × 0.2 cm hydrogel cubes;
[0074] (3) placing a silicone mold with a size of 1×1×0.2 cm on a graphite electrode, injecting the uniform viscous solution of step (1) into the mold, and covering it with a graphite electrode, placing another silicone mold on the above graphite electrode, placing the hydrogel block cut from step (2) into the mold, and finally covering it with a graphite electrode to form an electrode sheet-ion thermoelectric gel-electrode sheet-ion thermoelectric gel-electrode sheet stacked structure (such as Figure 1 As shown), and finally encapsulated with polyethylene film to obtain a laminated ion thermoelectric gel battery.
[0075] Comparative Example 2
[0076] This comparative example provides a laminated ion thermoelectric gel battery, and its preparation method is as follows:
[0077] (1) 3 g of gelatin, 0.3954 g of potassium ferrocyanide (final concentration of 0.15 mol / L), and 0.8446 g of potassium ferrocyanide (final concentration of 0.25 mol / L) were weighed and added to 8 mL of Wahaha water to obtain a mixture; then, the mixture was placed at 70° C. and heated with stirring at 600 rpm until dissolved and a viscous liquid was formed;
[0078] (2) Weigh 0.5 g of polyvinyl alcohol, 0.071 g of sodium sulfate (final concentration of 0.10 mol / L), and 0.189 g of sodium sulfite (final concentration of 0.30 mol / L), add 5 mL of Wahaha water, stir at 90 °C for 2 h, mix well, transfer to a 5 × 5 × 0.2 cm mold, and then place it at -20 °C for 24 h, thaw at room temperature for 3 h to obtain polyvinyl alcohol (PVA) hydrogel, and then cut it into 1 × 1 × 0.2 cm hydrogel cubes;
[0079] (3) placing a silicone mold with a size of 1×1×0.2 cm on a graphite electrode, injecting the uniform viscous solution of step (1) into the mold, and covering it with a graphite electrode, placing another silicone mold on the above graphite electrode, placing the hydrogel block cut from step (2) into the mold, and finally covering it with a graphite electrode to form an electrode sheet-ion thermoelectric gel-electrode sheet-ion thermoelectric gel-electrode sheet stacked structure (such as Figure 1 As shown), and finally encapsulated with polyethylene film to obtain a laminated ion thermoelectric gel battery.
[0080] Comparative Example 3
[0081] This comparative example provides a laminated ion thermoelectric gel battery, and its preparation method is as follows:
[0082] (1) 3 g of gelatin, 0.0791 g of potassium ferrocyanide (final concentration of 0.03 mol / L), and 1.0135 g of potassium ferrocyanide (final concentration of 0.30 mol / L) were weighed and added to 8 mL of Wahaha water to obtain a mixture; then, the mixture was placed at 70° C. and heated with stirring at 810 rpm until it dissolved and formed a viscous liquid;
[0083] (2) Weigh 0.5 g of polyvinyl alcohol, 0.213 g of sodium sulfate (final concentration of 0.30 mol / L), and 0.189 g of sodium sulfite (final concentration of 0.30 mol / L), add 5 mL of Wahaha water, stir at 90 °C for 2 h, mix well, transfer to a 5 × 5 × 0.2 cm mold, and then place it at -20 °C for 24 h, thaw at room temperature for 3 h to obtain polyvinyl alcohol (PVA) hydrogel, and then cut it into 1 × 1 × 0.2 cm hydrogel cubes;
[0084] (3) placing a silicone mold with a size of 1×1×0.2 cm on a graphite electrode, injecting the uniform viscous solution of step (1) into the mold, and covering it with a graphite electrode, placing another silicone mold on the above graphite electrode, placing the hydrogel block cut from step (2) into the mold, and finally covering it with a graphite electrode to form an electrode sheet-ion thermoelectric gel-electrode sheet-ion thermoelectric gel-electrode sheet stacked structure (such as Figure 1 As shown), and finally encapsulated with polyethylene film to obtain a laminated ion thermoelectric gel battery.
[0085] Comparative Example 4
[0086] This comparative example provides a laminated ion thermoelectric gel battery, and its preparation method is as follows:
[0087] (1) 3 g of gelatin, 0.7908 g of potassium ferrocyanide (final concentration of 0.30 mol / L), and 0.5068 g of potassium ferrocyanide (final concentration of 0.15 mol / L) were weighed and added to 8 mL of Wahaha water to obtain a mixture; then, the mixture was placed at 70° C. and heated with stirring at 810 rpm until dissolved and a viscous liquid was formed;
[0088] (2) Weigh 0.5 g of polyvinyl alcohol, 0.1420 g of sodium sulfate (final concentration of 0.20 mol / L), and 0.0945 g of sodium sulfite (final concentration of 0.15 mol / L), add 5 mL of Wahaha water, stir at 90 °C for 2 h, mix well, transfer to a 5 × 5 × 0.2 cm mold, and then place it at -20 °C for 24 h, thaw at room temperature for 3 h to obtain polyvinyl alcohol (PVA) hydrogel, and then cut it into 1 × 1 × 0.2 cm hydrogel cubes;
[0089] (3) placing a silicone mold with a size of 1×1×0.2 cm on a graphite electrode, injecting the uniform viscous solution of step (1) into the mold, and covering it with a graphite electrode, placing another silicone mold on the above graphite electrode, placing the hydrogel block cut from step (2) into the mold, and finally covering it with a graphite electrode to form an electrode sheet-ion thermoelectric gel-electrode sheet-ion thermoelectric gel-electrode sheet stacked structure (such as Figure 1 As shown), and finally encapsulated with polyethylene film to obtain a laminated ion thermoelectric gel battery.
[0090] Battery Characterization
[0091] 1. The thermoelectric potential test was performed on the laminated ion thermoelectric gel batteries of Examples 1-3 and Comparative Examples 1-4. Figure 3 As shown, the open circuit voltage of the laminated ion thermoelectric gel battery prepared has a corresponding relationship with the temperature difference, and the slope after linear fitting is the corresponding thermoelectric potential, wherein the corresponding thermoelectric potential of Example 1 is 8.5 mV K-1 The corresponding thermoelectric potential of Example 2 is 6.3 mV K -1 The corresponding thermoelectric potential of Example 3 is 6.1 mV K -1 The corresponding thermoelectric potentials of Comparative Examples 1-4 are 5.12 mV K -1 、5.5mVK -1 , 4.8mV K -1 , 3.21mV K -1 The above experimental results show that the water-soluble metal salt in the ionic thermoelectric gel can enable the laminated ionic thermoelectric gel battery to obtain excellent thermoelectric potential values. In particular, Example 1 uses organic metal salts to regulate the laminated ionic thermoelectric gel battery, and its thermoelectric potential value is greatly improved compared to the comparative example.
[0092] 2. The output power density of the laminated ion thermoelectric gel battery of Examples 1-3 and Comparative Examples 1-4 is tested. One electrode of the laminated ion thermoelectric gel battery is at the hot end, and the other electrode is at the cold end. The hot end and the cold end are closely connected to the upper and lower electrodes. By controlling the temperature of the hot end and the cold end, different temperature differences are achieved. The output power density of the thermoelectric power generation device under a temperature difference of 5K is tested under a temperature condition of 313K. Figure 4 As shown in FIG. 1 , the output power density of the laminated ion thermoelectric gel battery prepared according to Example 1 at a temperature difference of 5K is 602.5 mW m -2 The output power density of Example 2 is 352.5 mW m -2 The output power density of Example 3 is 330 mW m -2 The output power densities of comparative examples 1-4 are 202.5 mW m -2 、250.0mW m -2 、180mW m -2 、170mW m -2 The above experimental results show that the water-soluble metal salt in the ionic thermoelectric gel can enable the laminated ionic thermoelectric gel battery to obtain excellent output power density. In particular, Example 1 uses organic metal salts to regulate the laminated ionic thermoelectric gel battery, and its output power density is greatly improved compared with the comparative example.
[0093] 3. The energy density of the laminated ion thermoelectric gel batteries of Examples 1-3 and Comparative Examples 1-4 was tested. The energy density obtained by discharging with a 7500Ω resistor for 2 hours at a temperature difference of 35K is as follows: Figure 5 As shown in the figure, the energy density of the laminated ion thermoelectric gel battery prepared in Example 1 is 92.11 J m -2 The energy density of Example 2 is 80.1 J m -2 The energy density of Example 3 is 81.3 J m -2The energy densities of comparative examples 1-4 are 74.1 J m -2 、75.3J m -2 、69.7J m -2 、68.3Jm -2 The above experimental results show that the water-soluble metal salt in the ionic thermoelectric gel can enable the laminated ionic thermoelectric gel battery to obtain excellent energy density. In particular, Example 1 uses organic metal salts to regulate the laminated ionic thermoelectric gel battery, and its energy density is greatly improved compared with the comparative example.
[0094] 4. Make a temperature difference power generation device and a wearable device using the laminated ion thermoelectric gel battery prepared in Example 1. Connect 9 laminated ion thermoelectric gels in series with copper electrodes to obtain a temperature difference power generation device, wherein one electrode of the temperature difference power generation device is at the hot end, and the other electrode is at the cold end. The hot end and the cold end are tightly connected to the upper and lower electrodes. By controlling the temperature of the hot end and the cold end, different temperature differences can be achieved. The temperature difference power generation device is placed at 313K, and a temperature difference of 5K is applied to the hot end and the cold end. The output voltage obtained is 1.355V (such as Figure 6 The output power density is 130 mW m -2 .(like Figure 7 shown).
[0095] Traditional electronic semiconductor thermoelectric materials require hundreds or thousands of thermoelectric legs to achieve a voltage of 1V, while the laminated ion thermoelectric gel battery of the present invention only requires 9 in series to achieve a voltage of 1.355V at a temperature difference of 5K.
[0096] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A laminated ion thermoelectric gel battery, characterized in that: It comprises an electrode 1, an ionic thermoelectric gel 1, a built-in electrode, an ionic thermoelectric gel 2 and an electrode 2 which are arranged in sequence; the raw materials for preparing the ionic thermoelectric gel 1 comprise a gelling matrix, a water-soluble metal salt 1, a redox couple 1 and water; the raw materials for preparing the ionic thermoelectric gel 2 comprise a gelling matrix, a redox couple 2 and water; the redox couple 1 and the redox couple 2 are of different types.
2. The laminated ion thermoelectric gel battery according to claim 1, characterized in that: The redox couple 1 and the redox couple 2 are independently selected from K3Fe(CN)6 / K4Fe(CN)6 or Na2SO4 / Na2SO3.
3. The laminated ion thermoelectric gel battery according to claim 1, characterized in that: The gelling matrix is selected from at least one of gelatin, polyvinyl alcohol, carrageenan, chitosan and polyacrylamide.
4. The laminated ion thermoelectric gel battery according to claim 1, characterized in that: The water-soluble metal salt 1 is selected from an inorganic metal salt or an organic metal salt; And / or, the raw materials for preparing the ionic thermoelectric gel 2 also include a water-soluble metal salt 2; the concentration of the water-soluble metal salt 1 in the ionic thermoelectric gel 1 is greater than the concentration of the water-soluble metal salt 2 in the ionic thermoelectric gel 2; the water-soluble metal salt 2 is selected from an inorganic metal salt or an organic metal salt.
5. The laminated ion thermoelectric gel battery according to claim 4, characterized in that: The inorganic metal salt is at least one of sodium chloride, potassium chloride, potassium nitrate and potassium sulfate; the organic metal salt is at least one of potassium trifluoromethanesulfonate, potassium citrate and sodium oxalate.
6. The laminated ion thermoelectric gel battery according to claim 1, characterized in that: The raw materials for preparing the ionic thermoelectric gel 1 meet one or more of the following conditions: A) the ratio of the gel matrix to the redox couple 1 is 1 g: (1-10) mmol; B) the ratio of the gel matrix to the water-soluble metal salt 1 is 1 g: (1-10) mmol; C) The usage ratio of the gel matrix to water is 1 g: (5-20) mL. And / or, the raw materials for preparing the ionic thermoelectric gel 2 meet one or more of the following conditions: D) the ratio of the gel matrix to the redox couple 2 is 1 g: (0.3-2) mmol; E) The usage ratio of the gel matrix to water is 1 g: (2-5) mL.
7. The laminated ion thermoelectric gel battery according to claim 1, characterized in that: The electrode 1 and the electrode 2 are independently selected from at least one of graphite paper, carbon paper and carbon cloth; And / or, the built-in electrode is selected from at least one of graphite paper, carbon paper, carbon cloth, and a cation exchange membrane.
8. The method for preparing the laminated ion thermoelectric gel battery according to claims 1-7, characterized in that: The following steps are involved: After placing the ionic thermoelectric gel 1 on the surface of the electrode 1, the built-in electrode is covered on the surface of the ionic thermoelectric gel 1 away from the electrode 1, the ionic thermoelectric gel 2 is arranged on the surface of the built-in electrode away from the ionic thermoelectric gel 1, and the electrode 2 is arranged on the surface of the ionic thermoelectric gel 2 away from the built-in electrode, to obtain a laminated ionic thermoelectric gel battery with the electrode 1, ionic thermoelectric gel 1, built-in electrode, ionic thermoelectric gel 2 and electrode 2 arranged in sequence.
9. The method for preparing the laminated ion thermoelectric gel battery according to claim 8, characterized in that: The preparation method of the ionic thermoelectric gel 1 comprises the following steps: mixing a gelling matrix, a water-soluble metal salt 1 and a redox couple 1 in water to obtain a paste gel 1, and then preparing the ionic thermoelectric gel 1; And / or, the method for preparing the ionic thermoelectric gel 2 comprises the following steps: mixing a gelling matrix and a redox couple 2 in water to obtain a paste gel 2, and then preparing the ionic thermoelectric gel 2.
10. A temperature difference power generation device, characterized in that: The invention comprises the laminated ion thermoelectric gel battery as described in claims 1-7.
Citation Information
Patent Citations
Method for preparing flexible self-driven temperature / pressure sensor by adopting thermoelectric gel
CN114754889A
Anion regulation type ion thermoelectric gel battery and preparation method and application thereof
CN117199415A
Method for manufacturing flexible thermoelectric device, and flexible thermoelectric device obtained by same
WO2023168942A1